Absolute Quantification of Choline-Related Biomarkers in Breast Cancer Biopsies by Liquid Chromatography Electrospray Ionization Mass Spectrometry - Maria Chiara Mimmi; Nicoletta Finato; Gloria Pizzolato; Carlo Alberto Beltrami; Federico Fogolari; Alessandra Corazza; Gennaro Esposito (Analytical Cellular Pathology, 2013)
It has been repeatedly demonstrated that choline metabolism is altered in a wide variety of cancers. In breast tumours, the choline metabolite profile is characterized by an elevation of phosphocholine and total choline-compounds. This pattern is increasingly being exploited as biomarker in cancer diagnosis.